2006
DOI: 10.1074/mcp.d500013-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Concanavalin A-captured Glycoproteins in Healthy Human Urine

Abstract: Both the urinary proteome and its glycoproteome can reflect human health status, and more directly, functions of kidney and urinary tracts. Because the high abundance protein albumin is not N-glycosylated, the urine N-glycoprotein enrichment procedure could deplete it, and urine proteome could thus provide a more detailed protein profile in addition to glycosylation information especially when albuminuria occurs in some kidney diseases. In terms of describing the details of urinary proteins, the urine glycopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 13 publications
1
80
0
1
Order By: Relevance
“…Wang et al [6] identified 225 N-glycoproteins in Con-A enriched normal human urinary proteome, whereas Li et al [4] identified 31 phosphoproteins.…”
Section: Profiling Of Normal Human Urinary Proteomementioning
confidence: 99%
“…Wang et al [6] identified 225 N-glycoproteins in Con-A enriched normal human urinary proteome, whereas Li et al [4] identified 31 phosphoproteins.…”
Section: Profiling Of Normal Human Urinary Proteomementioning
confidence: 99%
“…Large scale proteomics profiling of normal human urine samples has revealed the presence of at least 1000 different protein gene products and many more peptide fragments of larger proteins (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). There is hope, therefore, for discovery of urinary protein excretion profiles that can be used clinically for tasks such as early detection of disease, classification of disease, choice of therapeutic agents, assessment of prognosis, and monitoring of a particular therapeutic regimen.…”
mentioning
confidence: 99%
“…Urine is potentially a rich source for N-and Olinked glycoproteins derived from renal-and distal organs and represents an interesting subproteome for structural charac-terization of human glycoproteins. However, glycoproteomic characterization of urine is lacking and only a few proteomic studies aimed at identifying urinary glycoproteins have been reported (17)(18)(19)(20). In these studies, the glycan moieties were either cleaved off or not studied at all.…”
mentioning
confidence: 99%